Fluorescence studies of aldol catalysis and vapor plotting of chemically graded films - Bautista Gomez, Judith (Kansas State University, 2020)
Aldol reactions are the most versatile of organic reactions and are widely used synthetic routes to carbon-carbon bond formation via the coupling of ketones and aldehydes. The synthesis of pharmaceuticals, industrial feedstocks, commodity chemicals, and biomass-derived renewable liquid fuels frequently involve aldol reactions. These reactions are mainly catalyzed by strong bases (i.e. hydroxides), which are corrosive, not easily recovered, and not re-usable, leading to excess waste. Due to these difficulties, heterogeneous catalysts have gained interest among researchers in efforts to develop clean and economical processes. A better understanding of how the chemical and structural properties of heterogeneous catalysts lead to aldol product formation will enable their use in eco-friendly industrial processes. This dissertation describes work directed towards an improved understanding of heterogeneous aldol reaction catalysts. As part of this work, the synthesis of a new Nile Red derivative incorporating a reactive aldehyde moiety (NR-Al) to follow aldol reactions is described. The dye was used to follow aldol reactions catalyzed by mesoporous and thin film materials. Ensemble and single molecule fluorescence spectroscopic methods were employed to characterize catalyst activity. The unique properties of NR-Al enabled, for the first time, preliminary studies of individual aldol reaction events occurring in real time at the single molecule level. The results presented in this dissertation will facilitate a broad range of both ensemble and single molecule spectroscopic investigations of heterogeneous catalysis in aldol reactions in the future. The work in this dissertation involved three distinct studies. In the first study, NR-Al was synthesized and characterized by High Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) and proton and carbon Nuclear Magnetic Resonance spectroscopy (¹H and ¹³C NMR). The dye was employed to follow aldol reactions in situ. A heterogeneous acid-base bifunctional catalyst of magnesium-zirconium-cesium supported on fumed silica (Mg-Zr-Cs/SiO₂) was employed, as was a strong base catalyst of magnesium-oxide (MgO); fumed silica (SiO₂) was employed as a control. Acetone and acetophenone were employed for crossed-aldol reactions with NR-Al at room temperature. The fluorescence spectral shifts observed from NR-Al during these reactions revealed whether each stopped at the alcohol addition product alone or instead formed both the aldol addition and olefin condensation products. Aldol product formation was verified by HPLC-MS and confirmed that the basic MgO catalyst only catalyzed primarily addition product formation, while the acid-base bifunctional catalyst, Mg-Zr-Cs/SiO₂, proceeded to olefin product formation. A mechanism that was based on the observed results and related literature was proposed to explain these observations. Olefin product formation in the case of Mg-Zr-Cs/SiO₂ was concluded to result from cooperativity between weak acid and base sites on the catalyst. In the second study, NR-Al-doped catalyst films obtained by a sol-gel process using tetramethylorthosilicate (Mg-Zr-Cs/TMOS) were employed for aldol catalysis. Spectroscopic ellipsometry (SE) and X-ray Photoelectron Spectroscopy (XPS) were used to verify that a thin film was deposited, and that the active cesium component was well dispersed within the film. Widefield fluorescence microscopy and single molecule spectroscopy imaging and tracking methods were employed to show, for the first time, that NR-Al and the products of its aldol reactions with acetone and acetophenone are sufficiently fluorescent to be detected at the single molecule level. Preliminary studies showed that it may be possible to detect individual aldol reaction events from acetone vapor condensing and reacting with a NR-Al-doped catalyst film in real time. In the third study, a direct-write method based on vapor phase plotting of organosilane precursors was developed and demonstrated. This method allowed for patterned uniform or gradient chemical films to be prepared over selected substrate regions, without modifying neighboring areas. Plotting parameters such as ambient relative humidity, chemical concentration, raster scanning speed, and capillary-substrate separation were all found to influence surface coverage and plotting resolution. The optimized plotting parameters were employed for initial demonstrations in which chemical pads and gradients were plotted using n-octyltrichlorosilane and 3-cyanopropyltrichlorosilane in separate experiments. The chemical pads and gradients were characterized by Water Contact Angle (WCA), SE, and by XPS. In this initial work, millimeter scale spatial resolution was achieved using glass capillaries with millimeter inner diameters. With certain modifications to the current system, this vapor phase plotting method can likely be used in the production of patterned coatings for biological, optical, and microelectronic devices, as well as in the preparation of catalysts for aldol reactions.
Keywords: Aldol catalysis; Vapor plotting; Fluorescence spectroscopy; Organic/inorganic thin films; Heterogeneous catalysts